2004
DOI: 10.1128/jcm.42.3.1305-1307.2004
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Diversity of Norovirus and Sapovirus in Hospitalized Infants with Sporadic Cases of Acute Gastroenteritis in Chiang Mai, Thailand

Abstract: Stool specimens from hospitalized infants with sporadic gastroenteritis in Chiang Mai, Thailand, between July 2000 and July 2001 were examined for norovirus and sapovirus by reverse transcription-PCR and sequence analysis. These viruses were identified in 13 of 105 (12%) specimens. One strain was found to be a recombinant norovirus

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
117
2

Year Published

2005
2005
2013
2013

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 137 publications
(137 citation statements)
references
References 19 publications
(16 reference statements)
18
117
2
Order By: Relevance
“…The rate of SaVs obtained in Belém was similar to those reported in Thailand and Australia (4.8% and 4.1%, respectively) and lower than rates in India 20,21,35 (10.2%)…”
Section: Fromsupporting
confidence: 59%
“…The rate of SaVs obtained in Belém was similar to those reported in Thailand and Australia (4.8% and 4.1%, respectively) and lower than rates in India 20,21,35 (10.2%)…”
Section: Fromsupporting
confidence: 59%
“…A similar occurrence of these viruses in male and female children in different age groups is described in the literature (Kaplan et al 1982) although there is a higher rate of occurrence of these viruses in children up to 12 months of age (Pang et al 1999, Rockx et al 2002, Hansman et al 2004.…”
Section: Discussionmentioning
confidence: 70%
“…The results from the hospital population are consistent with those from similar studies conducted in other developing and developed countries. In a report from Thailand, 12% of stool specimens were positive for NoVs [Hansman et al, 2004a]. Reports from Malawi, China, Vietnam, Mongolia, and India [Kang et al, 2000;Hansman et al, 2004bHansman et al, , 2005Dove et al, 2005;Liu et al, 2006], have reported NoVs associated with 6-25% of acute gastroenteritis cases.…”
Section: Discussionmentioning
confidence: 99%